Evaluation Flood Disaster Management System in Primary Health Centers in East Java - Ani Sutriningsih; Vita Maryah Ardiyani; Wahyu Dini Metrikayanto; Sri Haryuni; Ika Rahmawati (Universitas STRADA Indonesia, 2026)
Background: Floods are the most frequent disasters in Indonesia, namely 3885 since 1815-2019. The cause of the high morbidity and mortality rates due to floods is the disruption of the continuity of Primary Health Centers services during a disaster. Primary Health Centers play a role in disaster management which includes pre-disaster, during disaster, and post-disaster. Purpose: This study examines the flood disaster management system at Primary Health Centers. Methods: This quantitative descriptive study involved 60 flood-prone Primary Health Centers in East Java. The instrument used to measure the role of Primary Health Centers is a questionnaire. The questionnaire contained 18 indicators. Seven indicators were used in the pre-disaster phase, five in the during-disaster phase, and six in the post-disaster phase. Data analysis was performed using frequency distribution and mean ± standard deviation. Results: The distribution of disaster management systems shows the highest average value in the pre-disaster stage (4.28), followed by the post-disaster stage (3.80), and the disaster stage (3.65). The three stages have the same median value, namely 4.00, with the largest data variation seen in the post-disaster stage (standard deviation 2.916). Conclusion: Practical implications for disaster preparedness policies at Primary Health Centers include developing emergency plans, routine training for health workers, and providing adequate emergency infrastructure. This policy ensures that primary health care facilities remain ready and responsive in the event of a crisis.